2022
DOI: 10.3390/jof8100987
|View full text |Cite
|
Sign up to set email alerts
|

Living Fungi in an Opencast Limestone Mine: Who Are They and What Can They Do?

Abstract: Opencast limestone mines or limestone quarries are considered challenging ecosystems for soil fungi as they are highly degraded land with specific conditions, including high temperature, prolonged sunlight exposure, and a lack of organic matter, moisture, and nutrients in soil. In such ecosystems, certain fungi can survive and have a crucial function in maintaining soil ecosystem functions. Unfortunately, we know very little about taxonomic diversity, potential functions, and the ecology of such fungi, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Few studies have analyzed the fungal community structure of environments impacted by mining activities, with Basidiomycota and Ascomycota being the dominant phyla (53,54). Here we observed that Ascomycota dominated pristine soil and topsoil, followed by Basidiomycota while Basidiomycota outnumbered Ascomycota in freshly prepared or vegetated technosoil (55).…”
Section: Discussionmentioning
confidence: 57%
“…Few studies have analyzed the fungal community structure of environments impacted by mining activities, with Basidiomycota and Ascomycota being the dominant phyla (53,54). Here we observed that Ascomycota dominated pristine soil and topsoil, followed by Basidiomycota while Basidiomycota outnumbered Ascomycota in freshly prepared or vegetated technosoil (55).…”
Section: Discussionmentioning
confidence: 57%